SEJARAH TUAN GURU BASSALAM: Syekh Abdul Wahab Rokan - Ricu Sidiq; Dwi Ryzki Adyanti; Miftahul Jannah; Masroito Siregar; Nurhaliza Nurhaliza (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
Sheikh Abdul Wahab Rokan Al-Khalidi Naqsyabandi is a prominent scholar, Wali Allah, leader of Tariqat Naqsaybandiah, Freedom Fighter and known as Tuan Guru Babussalam. He was born in the village of Danau Runda, Rantau Binuang Sakti Village, Negeri Tinggi, Kecepatan District, Rokan Hulu Regency, Riau. Tuan Guru was born on the 10th of Rabi'ul Akhir 1230 H (28 September 1811). He has a good morals, diligent worship, and always implement God's command. At the moment his mother had died at the time he was 2 years old he was then sorted by his father and his father became the first madrasah he knew and studied religious science. He stayed on the langkat at the offer of the sultan of Moses, and he gave up the area above the bug sei to be the home of sheikh abdul wahab and his followers and a village called "babussalam”.He herself indicate the science of religion and other ones never left behind his education. This study aims to find out how the journey of the story of a Sheikh Abdul Wahab Rokan in North Sumatra. This study uses a research method used is a historical research method consisting of Heuristics, Source Criticism, Interpretation and Historiography.